Effect of treatment zone decentration on axial length growth after orthokeratology - Zhang, Shuxian; Zhang, Hui; Li, Lihua; Yang, Xiaoyan; Li, Shumao; Li, Xuan (Frontiers in Neuroscience, 2022)
Objective: To study the effect of treatment zone (TZ) decentration on axial length growth (ALG) in adolescents after wearing the orthokeratology lenses (OK lenses). Methods: This retrospective clinical study selected 251 adolescents who were fitted OK lenses at the Clinical College of Ophthalmology, Tianjin Medical University (Tianjin China) from January2018–December 2018 and wore them continuously for >12 months. The age of the subjects was 8–15 years, spherical equivalent (SE): -1.00 to -5.00 diopter (D), and astigmatism ≤1.50 D. The corneal topography was recorded at baseline and 1-, 6-, and 12-month visits, and the axial length (AL) were recorded at baseline and 6-, 12-month visits. The data of the right eye were collected for statistical analysis. Results: The subjects were divided into three groups according to the decentration distance of the TZ after wearing lenses for 1 month: 56 cases in the mild (<0.5 mm), 110 in the moderate (0.5–1.0 mm), and 85 in the severe decentration group (>1.0 mm). A significant difference was detected in the ALG between the three groups after wearing lenses for 6 and 12 months (F=10.223, P<0.001; F=13.380, P<0.001, respectively). Among these, the 6- and 12-month ALG of the mild decentration group was significantly higher than that of the other two groups. Multivariable linear regression analysis showed that age, baseline SE, and 1-month decentration distance associated with the 12-month ALG (P<0.001, P<0.001, and P=0.001, respectively). Conclusion: The decentration of the TZ of the OK lens affected the growth of the AL in adolescents, i.e., the greater the decentration, the slower the ALG.